Motivasi Guru Pendidikan Agama Islam Menjadi Tenaga Pendidik Honorer Di Sekolah Menengah Kejuruan Negeri 13 Malang - Subhan adi santoso (VICRATINA, 2018)
National education function to develop the ability and form the character and civilization of dignified nation in order to educate the life of the nation, aims to develop the potential of learners to become human beings who believe and piety to God Almighty, noble, healthy, knowledgeable, capable, creative, independent , and become a democratic and responsible citizen. To achieve these goals the education needs to be preceded by an adequate educational process. This research uses descriptive-qualitative paradigm approach. Data Collection Techniques Include: Interview Method, Observation or Observation Method and Documentation Method. research results Factor of pride and bonding of a teacher becomes stronger when, found many students from among the poor who can actually compete from Siwa who come from upper middle class. Here will increase the spirit of teachers to serve even more strongly devote himself, although with a mediocre salary.